Functional Phenotypes of Peritoneal Macrophages Upon AMD3100 Treatment During Colitis-Associated Tumorigenesis - Wu, Shuai; Luo, Weiwei; Wu, Xing; Shen, Zhaohua; Wang, Xiaoyan (Frontiers in Medicine, 2022)
CXCL12 and its receptor CXCR4 are independent prognostic factors in colorectal cancer. AMD3100 is the most frequently used FDA-approved antagonist that targets the CXCL12-CXCR4 axis in clinical trials. We aimed to explore the role of AMD3100 and its effect on peritoneal macrophages’ functional phenotypes during colitis-associated tumorigenesis. We treated AMD3100 in a colitis-associated colon cancer mouse model and evaluated its effect on tumorigenesis. The phagocytosis activities of peritoneal macrophages were measured by flow cytometry. The proportions of macrophages and M1/M2 subpopulations were investigated by flow cytometry, ELISA, and immunochemistry. Serum levels of pro-inflammatory and anti-inflammatory cytokines were measured by LEGENDplex™ kits. Transwell assay and qRT-PCR were performed to investigate the direct effect of CXCL12 on macrophages in vitro. We demonstrated that AMD3100 treatment reduced the inflammatory damages in the colonic mucosal and ameliorated tumor development in experimental mice. We found that the phagocytosis activities of peritoneal macrophages fluctuated during colitis-associated tumorigenesis. The proportions of peritoneal macrophages and M1/M2 subpopulations, together with their metabolite and cytokines, changed dynamically in the process. Moreover, AMD3100 regulated the functional phenotypes of macrophages, including reducing the phagocytosis and recruiting activity, promoting polarization to the M1 subpopulation, and reducing IL-12 and IL-23 levels in serum. Our study contributes to understanding dynamic changes of peritoneal macrophages upon AMD3100 treatment during tumorigenesis and sheds light on the potential therapeutic target of AMD3100 and peritoneal macrophages against colitis-associated colon cancer.